Leadership in Nursing - Dias, Carlos Manuel de Melo (2005)
Fiedler's Contingency Theory defines Leadership as a relationship in which power and influence are unevenly distributed, and whose efficiency depends on the contingency of the situation (the relationship between leader and group-members, the task structure and the power position of the leader). Moreover, Maslow's Human Motivation Theory defines Motivation as an organised set of five hierarchical levels of needs (physiological needs, safety needs, feeling of belonging needs, love and esteem needs, self-achievement needs). The hierarchy is arranged on the basis of relative potency, in which the lower level is always the basic level and also stronger than the immediate higher level and the superior level is more complex and differentiated than the lower level. The main purpose of this study consists in assessing which senior nursing officer leadership style allows group work effectiveness together with subordinate nurses' high level of motivation. In this study, we have applied a quantitative research approach, of a descriptive-analytic type, to data provided by questionnaires with anonymous answers given by nurses working in hospital wards. Six different scales were used: Leader Behaviour Description Questionnaire (studies the leader behaviour as described by subordinate nurses), Motivation Questionnaire (studies in which level of Maslow's hierarchical needs is the subordinate nurses' motivation placed), Least Preferred Co-Worker (studies the leader's description of the least preferred co-worker), Relationship between Leader and Members (studies the relationship's quality), Task Structure (studies task organisation and planning) and finally, Power Position (studies the leader's power over his/her subordinates). From the data analysed we could conclude that the subordinate nurse's motivation is focused on physiological needs (money, holidays, etc.) and on feeling of belonging (recognition, praise, etc.) much more than on self-fulfilment needs (being able to perform creative tasks or to develop one's skills), which would be desirable for differentiated and autonomous nursing professionals. On the other hand, the senior nursing officer perceives leadership as relationship orientated, whereas the leadership situation control is classified as high, which according to the Contingency Theory indicates group work inefficient performance. Therefore, firstly, this study acknowledges that the senior nursing officer's function in hospital ward practice is in value crisis, needing for clarification from the health organisations and other nursing professionals. Secondly, the non-valorisation of the subordinate nurses' motivation, as a whole, drives to the failure of personal self-fulfilment as well as group work fulfilment. Only with motivation criteria integrated in hospital human resources management will the organisational culture change and consequently staff satisfaction and good working results will be obtained. In conclusion, in order to find a solution for the current ineffective leadership practices of senior nursing officers, we suggest the adoption of the management measures recommended by Fiedler: leadership recruitment and selection, leadership training, and organisational engineering.